Sastra Daerah Yapen â Papua: Identifikasi Dan Deskripsi Dinamika Cerita Rakyat - Mora, Fersyd Dolfinus (Universitas Papua, 2017)
This article aims to reveal about the Yapen Papuan folklore associated with the identification and description of the story dynamics. This article can describe folklore as a part of regional literature that is still scattered in oral form and serves as the expression of the mind, attitudes, and cultural values of its supporters towards the formation of a more dignified personality. Other than that. This article seeks to illustrate the dissemination of folklore from various regions through the media is a means to socialize about the cultural content that is expected to foster mutual understanding or understanding the conditions of existence and diversity of cultural values reflected in the mindset and patterns of action among ethnic groups. This article constructs the Yapen-Papuan Peopleâs Story: Identification and Dynamics of Stories âthrough the stages of the identification and dynamics of this story relating to: (a) man, (b) animals, (c) plants, and (d) nature or the universe , And shaped legends, myths, and fairy tales.